Pemanfaatan Tanaman Lokal Serai (Cymbopogon Nardus) sebagai Spray Anti Nyamuk oleh Kader Pkk Kelurahan Pucang Sawit - Muhammad Sa'ad; Dwi Saryanti (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
One of the diseases that is still a health problem in Central Java Province is Dengue Hemorrhagic Fever (DHF). Surakarta is the city with the highest death rate (CFR) due to dengue fever in Central Java Province at 14.6%. Lack of knowledge and awareness of dengue fever is one of the causes of the high number of dengue fever cases. This service activity was carried out as an effort to prevent dengue fever by increasing community knowledge through Family Welfare Development (PKK) cadres regarding dengue fever and the use of herbal plants in the environment to prevent dengue fever. Community service was carried out in Pucang Sawit Village, Jebres, Surakarta which was attended by representatives from each Neighborhood Association (RT). Starting with counseling about dengue fever and the use of natural ingredients for dengue fever, especially the lemongrass plant, then continued with the practice of making repellent spray products from the lemongrass plant. Evaluation of the service implementation process is carried out by carrying out pre-tests and post-tests by service participants to determine the level of participants' knowledge of dengue fever and the use of Serai as a repellant, before and after service activities. The average pre-test and post-test scores obtained were 80.31 and 89.69 respectively. This value shows an increase in community knowledge before and after the extension activities were carried out.